The Role of TV Advertising in Promoting Children's Health Awareness During the Coronavirus Pandemic - Al-Azawi, Rana Abdul-Latif (Dirasat: Human and Social Sciences, 2024)
Objectives: This study examines the message framing and effectiveness of advertising in health awareness campaigns, with a focus on children. Methods: The study analyzed 11 health awareness ads related to the COVID-19 pandemic, broadcasted on the MBC3 channel from March to August 2020 using a comprehensive inventory analysis. Results: The results show that the health awareness campaign used three types of content to educate against the virus: prevention instructions (55%), precautionary information (35%), and general instructions on maintaining healthy habits (10%). The framing strategy of the health awearness campaign focused on delivering a specific message, either through health instructions or passing general health information. The investigated ads used simple steps in their strucutre to guide children to the required outcome of the infection, explaining the cause and effect of actions by showing the positive impact of staying home or social distancing in eliminating or minimizing the infection or the spread of the virus. There were no significant differences between the effectiveness of long and short ads in conveying the message to children. The ads used emotional advertising appeal, including strong imagery, impactful text, and powerful music. Conclusions: The study suggests that understanding the target audience is crucial for developing effective health awareness campaigns, and using simple language, appealing characters, and appropriate means of explanation can enhance the effectiveness of health awareness ads. The findings of this study have implications for designing future health awareness campaigns, especially those targeted towards children, to enhance their effectiveness in conveying health-related messages.